Variable theater space and synergy - Obracaj, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
Searching for the solution of the audience scene giving the widest possibilities of arrangement, was the domain of the 60s and 70s of the twentieth century. At that time, most of the projects and stage productions were created, where the basic relations of the game and observation areas were possible, so Baroque, Italian, Open and Arena. This tendency at the turn of the century has disappeared, but the renaissance of the Italian scene in various variations, with the principle of invariable form, sometimes with little possibility of transformations on the line opera – concert – dramatic theater. All these solutions generated huge costs by the need to use non-standard technical equipment, also significantly annoying exploitation. In 1996/1997 a reconstructed Shakespearean theater „Globe” was opened in London. This facility undoubtedly gave birth to a revived vision of contemporary dramatic theater. Spatial form, referring to antiquity, does not seem to be mobile staging. However, from the point of view of a particular viewer’s and actor’s relationship, using the appropriate directing criteria, the layout gains „internal” variability with virtually unchanged spatial layout. The idea of the renaissance theater of England is primarily applied in open, mass-scale buildings. Discussion is the solution in which the roof is used, or the background „linguistic” scenic substitute box scene. Eventually, the construction of the facility in heavy, reinforced concrete, rather than in light wood, results in lowering the „efficiency” of the staging, while the costs increase. The formal qualities of the Elizabethan Theater with technical requirements for the lighting base are generally acceptable in a wide range of repertoire. With the low cost of finance and the consistent cooperation of architects and stewards with their respective industries, the principle of synergy is fully met.